Findings from a UK–Morocco training programme to improve capacity in nutrition surveillance, research and education. (January 2017) - Mocciaro, G.; Ziauddeen, N.; Nicholson, S.; Almoosawi, S.; Ray, S.
Highlights: By the end of the workshop, several weaknesses, gaps, challenges and possible solutions have been identified. Via two questionnaires we have identified an increase in awareness and knowledge in nutrition and funding opportunities. A strong interest in creating new collaborations with researchers outside Morocco has been clearly shown.